Terapia Ocupacional basada en el Bienestar Social del Adulto Mayor del Centro de Atención Municipal “Los Arupos” Loja, en la actualidad - Lanche Capa, Alexandra Elizabeth (2025)
The objective of this research work was to analyze the influence of occupational therapy on the social welfare of the elderly in the “Los Arupos” Municipal Care Center, at present. This research was conducted with a qualitative approach, with a non-experimental, cross-sectional and descriptive design. The study population consisted of 20 older adults: 12 without cognitive impairment with whom semi-structured interviews were used and 8 with cognitive impairment to whom an observation guide was applied. The results showed that occupational therapy plays a fundamental role in promoting social well-being and thus the quality of life of older adults. The users of the center mentioned how these activities have helped their self-esteem, increasing their confidence and strengthening social cohesion and integration. In this sense, the center's users went from feeling isolated to becoming part of an active and numerous group. The activities they carry out at the center are not only therapeutic, but have also provided them with a space of confidence, motivation and security where they feel useful, accompanied and valued. Finally, it was concluded that Occupational Therapy significantly favors the reduction of isolation and loneliness, promoting the initiation of new friendships and the strengthening of social bonds. These activities not only benefit the emotional and social well-being of the users, but also highlight the relevance of creating programs that mix these therapeutic activities with opportunities for social integration. This confirms the importance of continuing to carry out initiatives that promote active and healthy aging according to the needs of each older adult